The relationship between CFO qualifications and internal control weakness - Yaying C. Yeh; Chiulien C. Venezia; Tzu-Ya Yang (Financial Internet Quarterly, 2022)
This study explores the relationship between CFO qualifications and a firm's internal control weakness (ICWs). We use three measures for CFO competence: financial/accounting back- ground, seniority, and education. Using a sample of Taiwanese listed firms from 2012 to 2015, the results of this study show a negative relationship between CFO financial/accounting back- ground and seniority with internal control weakness, indicating firms with higher quality CFOs experience a lower number of ICWs. CFO education level, however, is not related with a firm's internal control weakness. The results imply that capable CFOs can effectively implement a good internal system. The result of this study provides practical and policy implications.
Keywords: M4; M12; 330; CFO qualification; Financial Accounting background; CFO competence; Seniority; Internal control weakness